4x-2=6t+6

Simple and best practice solution for 4x-2=6t+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2=6t+6 equation:


Simplifying
4x + -2 = 6t + 6

Reorder the terms:
-2 + 4x = 6t + 6

Reorder the terms:
-2 + 4x = 6 + 6t

Solving
-2 + 4x = 6 + 6t

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 4x = 6 + 2 + 6t

Combine like terms: -2 + 2 = 0
0 + 4x = 6 + 2 + 6t
4x = 6 + 2 + 6t

Combine like terms: 6 + 2 = 8
4x = 8 + 6t

Divide each side by '4'.
x = 2 + 1.5t

Simplifying
x = 2 + 1.5t

See similar equations:

| 23=35-x | | 3y-x-5=20 | | d^6y/(dx)^6-d^3y/(dx)^3=0 | | 3(y+5)+6(y-4)+2= | | -5-6x=3-(x-5) | | -2x-6=2x+6. | | x=(3-2e^3)/(e^3-1) | | -10(x-1)=10-10x. | | -4x^2+19x-30=0 | | 6(x-1)=6x-1. | | 1-14+x/23=15 | | 3/4y-(y-1/3)=1/12(y-4) | | -4x^2-19x-30=0 | | 5.5=13-3x | | -2y+1=y-5. | | 8x-10y-7y+5x+11= | | y=-5/2x=3 | | 3x^2-6x+2= | | -7u-38=4(u+7) | | C=2.50y+13 | | Y=4x^2-15x-4 | | -9(x-1)=7x-39 | | 6-0+2/2= | | -6u+36=4(u+4) | | 25x-6+15*4=20x+10 | | 2(u+1)=6u-26 | | 14828.65=2*3.14*r^2+2*3.14r | | 3x+(4x-17)=4 | | 2y-20=6y-12 | | 5=1/2m+3. | | 11x^2-5x-36=0 | | z/9+5=10. |

Equations solver categories